2006
DOI: 10.1007/s00122-006-0460-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and characterization of FLC homologs and QTL analysis of flowering time in Brassica oleracea

Abstract: The FLC gene product is an inhibitor of flowering in Arabidopsis. FLC homologs in Brassica species are thought to control vernalization. We cloned four FLC homologs (BoFLCs) from Brassica oleracea. Three of these, BoFLC1, BoFLC3 and BoFLC5, have been previously characterized. The fourth novel sequence displayed 98% sequence homology to the previously identified gene BoFLC4, but also showed 91% homology to BrFLC2 from Brassica rapa. Phylogenetic analysis showed that this clone belongs to the FLC2 clade. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 43 publications
8
157
1
2
Order By: Relevance
“…Similarly, Okazaki et al (2007) reported that BoFLC2 plays a central role in the repression of flowering in B. oleracea (Okazaki et al 2007). Wang et al (2009) reported that BnC6FTa, the orthologous gene of BrFTa, was associated with the major QTL for flowering time in B. napus.…”
Section: Expression Analysis Of Brfta and Brflc2mentioning
confidence: 97%
“…Similarly, Okazaki et al (2007) reported that BoFLC2 plays a central role in the repression of flowering in B. oleracea (Okazaki et al 2007). Wang et al (2009) reported that BnC6FTa, the orthologous gene of BrFTa, was associated with the major QTL for flowering time in B. napus.…”
Section: Expression Analysis Of Brfta and Brflc2mentioning
confidence: 97%
“…One of the identified flowering time loci, VFR2, was mapped as a single Mendelian locus that overlaps precisely with BrFLC1 (Kole et al 2001). In B. oleracea, the gene associated with the largest genetic effect (36.8%) among flowering time QTL has been designated BoFLC2 (Okazaki et al 2007). The diploid Brassica genomes are three to five times larger than the Arabidopsis genome, which suggests that many flowering time QTL remain undiscovered.…”
mentioning
confidence: 99%
“…The polymorphism generation is due to the gap length between introns and promoters and varies between individual and species. This is being widely used in genetic map construction (Lin et al, 2005), QTL analysis (Okazakik et al, 2007), genetic diversity analysis , heterosis prediction , species identification, and other fields.…”
Section: Introductionmentioning
confidence: 99%